2022
DOI: 10.1002/deo2.132
|View full text |Cite
|
Sign up to set email alerts
|

Combined endoscopic mAnagement of BiliaRy and gastrIc OutLET obstruction (CABRIOLET Study): A multicenter retrospective analysis

Abstract: Objectives Combined biliary obstruction and gastric outlet obstruction (GOO) represent a challenging clinical scenario despite developments in therapeutic endoscopic ultrasonography (EUS) as GOO might impair EUS‐guided biliary drainage. Little is known about the effectiveness of different therapeutic combinations used to treat double obstruction, especially regarding stent patency. Methods All consecutive patients with double obstruction treated between 2016 and 2021 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Even after re‐establishing efficient gastroduodenal transit, some accumulation of food remnants and gastric juices in the prestenotic duodenal bulb may intermittently obstruct the LAMS. In line with recent data, patients with a combination of GOO and EUS‐CDS seem at higher risk for LAMS dysfunction, especially in those treated with enteral stents 32 . Alternatives such as EUS‐guided or percutaneous transpapillary stenting or EUS‐HGS may be preferred in these patients 33 …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Even after re‐establishing efficient gastroduodenal transit, some accumulation of food remnants and gastric juices in the prestenotic duodenal bulb may intermittently obstruct the LAMS. In line with recent data, patients with a combination of GOO and EUS‐CDS seem at higher risk for LAMS dysfunction, especially in those treated with enteral stents 32 . Alternatives such as EUS‐guided or percutaneous transpapillary stenting or EUS‐HGS may be preferred in these patients 33 …”
Section: Discussionmentioning
confidence: 54%
“…In line with recent data, patients with a combination of GOO and EUS-CDS seem at higher risk for LAMS dysfunction, especially in those treated with enteral stents. 32 Alternatives such as EUS-guided or percutaneous transpapillary stenting or EUS-HGS may be preferred in these patients. 33 Despite stent dysfunction, EUS-CDS remains an invaluable technique in case of failed/impossible ERCP in distal MBO.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a relatively strict, though clinically relevant, definition of stent dysfunction was used in the current study, including cholangitis as well as persistent or recurrent jaundice. Third, despite GOO being an exclusion criterion, three patients developed GOO during the course of the disease, which may have contributed to the occurrence of cholangitis [9,18]. Fourth, the use of LAMS with a relatively small diameter (6 × 8 mm) may have contributed, as currently there is some evidence that stents with larger diameters may reduce the risk of stent dysfunction [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, despite GOO being an exclusion criterion, 3 patients developed GOO during the course of the disease which may have contributed to the occurrence of cholangitis. [9,18] Fourthly, the use of a relatively small diameter LAMS (6x8mm) may have contributed, as there currently is some evidence that larger diameter stents may reduce the risk of stent dysfunction. [16] Lastly, in our study DPS were not routinely placed through the LAMS while recent data showed that this may be beneficial.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is probably the main reason explaining why the 28% of patients needed a complementary artificial nutrition at the end of follow-up in our study. An increased risk of GOO recurrence with ES versus EUS-GE has been recently described [ 24 ]. Similarly, there was only one patient with an EUS-GE dysfunction in our series (invasion of the stent by peritoneal carcinomatosis, 4%).…”
Section: Discussionmentioning
confidence: 99%